Role of Landscape Scale in the Distribution of Rodents in an Agroecosystem of Argentina - Fraschina, Jimena (2014)
The goal of this study was to assess the effect of the different habitats on rodent diversity, and to estimate the effect of changes in land use on the rodent abundance through different possible scenarios. We sampled poultry farms, human houses, riparian habitats, railway embankments, woodlots, pasture, crop fields and their borders. The habitats with highest frequency of captures were poultry farms and crop field borders, mainly because of Mus musculus and Akodon azarae captures, respectively. All rodent species were found in at least six of the nine habitats sampled, but in some of them with low frequency. The different habitats differed in their contribution to the abundance of each species. Crop fields and pasture borders contributed more than 40% to the abundance of A. azarae, Oxymycterus rufus, Oligoryzomys flavescens and Calomys musculinus, while poultry farms had higher abundance of M. musculus. Woodlots and railway embankments showed a high contribution to O. flavescens abundance. The increase in the area covered by crop fields and human habitats led to an increase in the abundance of M. musculus and Calomys spp. and to a decrease in the relative abundance of other species. Considering the role of habitat diversity in rodent diversity, our results suggest that none of the species studied, except M. musculus, which is highly dependent on farms, depends on a single habitat and that their abundance is supported by a variety of less perturbed habitats. The current changes in land use would generate an increase in M. musculus abundance in detriment of wildlife species which are associated with undisturbed habitats.